The Effectiveness of PAHE patch (ginger pandanus amaryllifolius extract compress) on the Level of Menstrual Pain in Adolescent Girls - Fitri, Dwi Elka; Lexi, Sri Agnes; Sari, Nova Nopita (Universitas Fort De Kock Bukittinggi, 2024)
Background: Adolescence is a period where sexual maturity occurs in adolescent girls, which is characterized by menstruation. Data shows that most adolescent girls in Indonesia experience menstrual pain. If left untreated, menstrual pain will cause interference in activities, especially learning activities. Therefore, therapy is needed that can help reduce menstrual pain. Pandan leaves and ginger are Indonesian herbal plants that have analgesic effects..Purpose: The purpose of this study was to determine the effectiveness of Pahe Patch (pandan ginger extract) on the level of menstrual pain in adolescents.Methods: The design of this research is Quasy Experiment using Non randomized Pretest-Postest with Control Group design. The sample in this study amounted to 30 intervention groups and 30 control groups with Proportional stratified sampling technique. The implementation of the study was carried out with a pre-test to measure the level of pain before being given intervention in the 2 groups, then given Pahe Patch twice a day for 1-3 days in the experimental group, while the control group to reduce pain researchers taught distraction techniques. Furthermore, a post-test was conducted to measure the pain level of respondents in both groupsResults: Data analysis will be carried out using paired sample T test and Independent sample T test. The results obtained Pvalue: 0.000 which is smaller than the alpha value (0.05. Conclusions)Conclusion: it can be concluded that PaHe Patch is effective in reducing menstrual pain in adolescent girls